2022
DOI: 10.3389/fpsyg.2022.962084
|View full text |Cite
|
Sign up to set email alerts
|

The road to green development: How can carbon emission trading pilot policy contribute to carbon peak attainment and neutrality? Evidence from China

Abstract: Carbon emission trading is not only a market-based instrument but also one of the government’s macro-policies, which is extremely crucial to fulfilling both carbon peak attainment and carbon neutrality goals. For this purpose, this paper adopts a 30-region dataset for the period from 2008 to 2020 in China and employs the difference-in-difference (DID) method to quantify the effect of the carbon emission trading pilot policy (CETP) on carbon emissions on the basis of introducing industrial structure upgrading a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…The research enriches existing studies from the perspective of heterogeneous effects. While numerous studies [17][18][19][20][21][22][23][24] have analyzed the carbon emission effects of CTPs, their conclusions built on homogeneous policy effects, often yielding results in an average sense. Our paper emphasizes the operational modes of carbon markets and the environmental differences faced by each pilot area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research enriches existing studies from the perspective of heterogeneous effects. While numerous studies [17][18][19][20][21][22][23][24] have analyzed the carbon emission effects of CTPs, their conclusions built on homogeneous policy effects, often yielding results in an average sense. Our paper emphasizes the operational modes of carbon markets and the environmental differences faced by each pilot area.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of national level carbon emission reduction rates, Zhang et al (2020) [21] found that those pilots demonstrate a faster (slower) rate of carbon emission reductions (or increases) in decoupled (non-decoupled) countries in comparison with countries that have not implemented the CTP. From the perspective of the spatial area, Lan et al (2020) [22] discovered that the CTP has a statistically significant mitigating effect on carbon emissions, with the impact gradually declining from the eastern to the central and, finally, to the western regions. Yi et al (2020) [23] revealed that the implementation of carbon markets in Beijing, Shanghai, and Hubei exhibited a significant inhibitory effect on local carbon emissions while having a promoting effect in Guangdong.…”
Section: Ctp's Carbon Emission Reduction Effects and Hypothesis Devel...mentioning
confidence: 99%
“…GCNs have been successfully used in fields such as social network analysis and recommendation systems. In green technology innovation research, GCNs can be used to analyze complex relationships between enterprises, industries, or regions to understand the spread and impact paths of green technology investments (Lan et al, 2022). This is valuable for an in-depth understanding of the cooperation and competition relationships between enterprises and the diffusion mechanism of green technology innovation (Aziz et al, 2021).…”
mentioning
confidence: 99%